Drainage and sewage system performance – Consequences of reductions in toilet flush volume. (September 2019) - Valencio, Isabella P; Gonçalves, Orestes M
This study aims to evaluate impacts of reducing toilet flush volume from 6.8 to 4.8 Lpf with laboratory and field studies. In laboratory, 260 tests were performed including water consumption, waste removal and solid transport tests, in 20 different toilets produced by national and international manufacturers. These tests demonstrated that a simple reduction in flush tank water level was not a viable solution for reducing flush volume, due to flush energy loss. Toilets are designed to work with certain water volume, and reducing this volume without studying the consequences that this could cause, can make with the toilet fail. Toilets approved according the standards ABNT NBR15097, ABNT NBR15491 and ASMEA112.19.2 were installed in 10 houses. The monitoring of water consumption and sewage system videos were conducted during eight months. When 6.8-Lpf toilets were installed, the average toilet water consumption was 16.6L/inhabitant/day. For 4.8-Lpf toilets, this value increased to 17.6. The number of flushes/person/day increased after toilets replacement, indicating that users applied successive flushes. Videos showed blockages in sewage system horizontal pipes. Findings from this study suggest that low-flush toilets do not decrease total water use, and may result in increased water use. In addition, they can cause clogging and solid deposit on sewage system. Practical application: Many management failures have affected the world water availability. Water demand has increased with population growth, and unless the equilibrium between water demand and supply is restored, the world will face increasing water shortage. However, it is essential to study the way of reducing water consumption. Without an effective analysis, instead of bringing benefits to population, water consumption reduction can lead to clogging and negative consequences on sewage system performance, causing disorder to them. It is recommended that manufacturers did not reduce the toilet water consumption without a study on the impact caused on the sewage systems, as well as designers should be careful when specifying sanitary appliances.